Democracia e islamismo en las transiciones políticas árabes (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
Considering the success of islamist political parties in the democratic elections that took place after the Arab revolutions, this article deals with the political nature and the historic development of those parties. It analizes the reasons why they emerged as the main actors of democratic change in the post-revolucionary transitions. It further studies the various national contexts (Morocco, Tunisia and Egypt) and its specific circumstances as well as the main challenges facing islamist governments in the building of democracy. It’s also analized the impact of the AKP Turkish model in the Arab islamist movements as well as in Arab societies at large.